2019
DOI: 10.1371/journal.pone.0222110
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for formal and traditional sources of childbirth and postnatal care among women in rural Africa: A systematic review

Abstract: BackgroundThe underutilization of formal, evidence-based maternal health services continues to contribute to poor maternal outcomes among women living in rural Africa. Women’s choice of the type of maternal care they receive strongly influences their utilization of maternal health services. There is therefore a need to understand rural women’s preferred choices to help set priorities for initiatives attempting to make formal maternal care more responsive to women’s needs. The aim of this review was to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 73 publications
0
29
0
Order By: Relevance
“…A literature review on Asian traditional beliefs and practices also described that cultural beliefs can influence women's use of formal maternal healthcare services, and that women's fear of unnecessary medical interventions was a barrier to institutional births [26]. In a review of childbirth and postnatal care in rural Africa, the authors found that the influencing factors of people's preferences regarding formal or traditional healthcare were related to perceived attitudes toward healthcare providers, accessibility to maternal care, and respect for cultural and religious norms [27]. The study also demonstrated that women across rural Africa prefer to receive childbirth care from caring, considerate, and sympathetic providers, and that this population group sees cruel, insensitive, and degrading attendants as increasing negative maternal experiences and outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review on Asian traditional beliefs and practices also described that cultural beliefs can influence women's use of formal maternal healthcare services, and that women's fear of unnecessary medical interventions was a barrier to institutional births [26]. In a review of childbirth and postnatal care in rural Africa, the authors found that the influencing factors of people's preferences regarding formal or traditional healthcare were related to perceived attitudes toward healthcare providers, accessibility to maternal care, and respect for cultural and religious norms [27]. The study also demonstrated that women across rural Africa prefer to receive childbirth care from caring, considerate, and sympathetic providers, and that this population group sees cruel, insensitive, and degrading attendants as increasing negative maternal experiences and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The study also demonstrated that women across rural Africa prefer to receive childbirth care from caring, considerate, and sympathetic providers, and that this population group sees cruel, insensitive, and degrading attendants as increasing negative maternal experiences and outcomes. A final remark from the cited study highlighted that the trust rural African women have in TBAs influenced the type of healthcare service they sought [27].…”
Section: Discussionmentioning
confidence: 99%
“… 30 Furthermore, the importance of religious beliefs and trust in God is emphasized in a systematic review in which researchers identified that women in rural areas in Africa preferred healthcare facilities where their religious beliefs were respected and religiously sensitive care was provided. 31 Understanding the patient’s cultural context and the importance of religious and spiritual factors are important process elements in PCC 5 including the level of healthcare, which can be improved by providing a supportive environment, respectful care, and an open and trusting dialog between women and midwives, even when resources are scarce. Safe, respectful, and compassionate care is important.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the accessibility and affordability of maternal and neonatal care services, some women still prefer assistance of TBAs during pregnancy, labour, childbirth and puerperium (Chi & Urdal 2018 ; Mulenga et al 2018 ; Ngomane & Mulaudzi 2012 ). The preference and choice of maternity care by pregnant women is influenced by factors such as cultural beliefs, long distance to the nearest health facilities, disrespectful and abusive maternity care and friendliness of TBAs (Adatara et al 2018 ; Fantaye, Gunawardena & Yaya 2019 ; Gurara et al 2019 ; Mulenga et al 2018 ). In Burundi and Northern Uganda, TBAs were selected as the first point of consultation by many pregnant women in times of crisis (Chi & Urdal 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, the TBAs were also involved in the provision of maternal and child health services as health promoters (Sulayman & Adaji 2019). In contrast, other women prefer hospital-based maternal healthcare services during pregnancy, labour and puerperium because of their religious beliefs (Fantaye et al 2019).…”
Section: Introductionmentioning
confidence: 99%